The Parent-SmalQ Indonesia surveillance content validation involves monitoring and verifying physical activity behavior, sleep patterns, and dietary intake in children - Mulyawan, Rizki; Nopembri, Soni; Kaloka, Pasca Tri; Chua, Terence Buan Kiong; Ting, Low Seow; Chia, Michael Yong Hwa (Jurnal Keolahragaan, 2025)
The 24-hour guidelines heavily consider the dietary intake, sleep patterns, and physical activity habits of children. This study aims to determine the validity of the Parent-SmalQ Indonesia content for each question item, facilitating clear communication, comprehension, and implementation as an assessment tool for investigating children's lifestyles, consists of physical activity habits, sleep patterns, and dietary intake (three domains). Methods: The research targets both children and their parents, integrating their behaviours into a cohesive unit of voluntary participants. This validity assessment employs the phases of the Content Validation Index (CVI) for specific computations. Resuls: The three evaluated indicators are generated from the clarity, relevance, and completeness of each question item, comprising a total of 20 questions, with 3 validation items for each question, derived from 6 domains (3 domains for children; 3 domains for parents). Results from content validation indicate that the CVI elements of clarity (0.80 > 0.78), relevance (0.85 > 0.78), and completeness (0.85 > 0.78) were satisfactory. Conclusion: The Parent-SmalQ Indonesia questionnaire has achieved an adequate level of validity as a tool for assessing physical activity habits, sleep patterns, and dietary consumption. The Parent-SmalQ Indonesia questionnaire, verified for content, can predict children's behavior based on parental behaviours about physical activity, sleep, and dietary intake.